Study of the 165Ho(n,2n)164Ho reaction at near threshold energies - Georgali, Efstathia; Patronis, N.; Anastasiadis, A.; Axiotis, M.; Eleme, Z.; Harissopulos, S.; Kalamara, A.; Karfopoulos, K.; Kokkoris, M.; Lagoyannis, A.; Peoviti, M.; Potiriadis, C.; et al. (HNPS Advances in Nuclear Physics, 2020)
The present work concerns the preliminary analysis for the study of the (n,2n) reaction channel of the 165Ho isotope at near threshold energies: 10.1, 10.4 and 10.7 MeV (Eth=8.04 MeV). The cross sections for the population of both the ground state (Jπ=1+) and the isomeric state (Jπ=6-, Eex=139.8 keV) of the 164Ho product-nucleus were measured at the afore mentioned energies via the activation technique relative to the 27Al(n,α)24Na and 197Au(n,2n)196Au reactions. The quasi-monoenergetic neutron beams were produced through the 2H(d,n)3He reaction in the 5.5 MV Tandem Van de Graaf accelerator of N.C.S.R ’’Demokritos’’. The preliminary experimental results are compared with theoretical predictions based on TALYS code.